Pelatihan Komunikasi Pariwisata Berbasis Media Sosial (Instagram) Di Kota Pagar Alam, Sumatera Selatan - Nella, Mietha; Sari, Dian Novita Fajar; Haryani, Deffi (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2023)
The purpose of this training is to build the knowledge and skills of Kompepar members in the form of behavior in using Instagram social media to promote tourist destinations in Pagaralam City. The method used in this training is face to face lectures on social media concepts, and the practice of using these media in promoting tourist attractions. The results achieved in this training are increasing the knowledge and skills of Kompepar members in using Instagram social media seen from the selection of content, participation in responses (likes), and participation in giving comments. In conclusion, the content most selected by Kompepar members from Instagram social media is information, entertainment, and education. The participation of Kompepar members in responding to